2009
DOI: 10.1093/ndt/gfp245
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-fibrotic activities of herbal compounds and herbs

Abstract: Five herbal compounds and three herbal extracts have in vitro anti-fibrotic activities. These data warrant further studies on these anti-fibrotic entities and suggest it a promising strategy to discover new anti-fibrotic drugs by screening more plant materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 32 publications
2
75
0
Order By: Relevance
“…It reduces fibronectin expression by suppressing p38 signaling in diabetic rats and in high glucose-treated mesangial cells (4,21). Emodin also suppresses IL-1β-induced ECM production in mesangial cells (5) and inhibits collagen I expression in rat fibroblasts (22). However, its mechanisms are not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…It reduces fibronectin expression by suppressing p38 signaling in diabetic rats and in high glucose-treated mesangial cells (4,21). Emodin also suppresses IL-1β-induced ECM production in mesangial cells (5) and inhibits collagen I expression in rat fibroblasts (22). However, its mechanisms are not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Picrosirius red staining allows the collagen produced by cell cultures to be quantified (Hu et al, 2009;Xu et al, 2007). Exposure of HK-2 cells to 50 and 5 mg/ml AS for 48 h did not modify the amount of collagen produced as compared to the control condition ( Figure 6).…”
Section: Cispt-induced Collagen Deposition Is Limited By As Co-treatmentmentioning
confidence: 98%
“…Next, cells were washed with PBS, fixed with ice-cold methanol for 1 h at 4 C, rinsed twice with 1% acetic acid and stained for 2 h with 0.1% picrosirius red (PSR) staining solution (Hu et al, 2009). Wells were then rinsed three times with 1% acetic acid.…”
Section: Assessment Of Collagen Synthesismentioning
confidence: 99%
“…In contrast to the lack of "anti-fibrotics" in Western medicine clinics, there is accumulating evidence suggesting anti-fibrotic effects of Chinese materia medicas (CMMs), i.e., medicinal materials used in traditional Chinese medicine (TCM) (Hu et al, 2007). However, most of these conclusions were drawn from animal models or patients and hence it was not clear whether the reported efficacy of those CMMs was secondary to inhibition of aetiological factors or inflammation, or whether they exerted genuine anti-fibrotic activities (Hu et al, 2009). We hypothesised that at least some of the "anti-fibrotic" herbal derivatives reported in the literature are indeed anti-fibrotic by antagonising TGF-1-specific pro-fibrotic pathways or common pathways of fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesised that at least some of the "anti-fibrotic" herbal derivatives reported in the literature are indeed anti-fibrotic by antagonising TGF-1-specific pro-fibrotic pathways or common pathways of fibrosis. By employing the 2D in vitro model , we tested the anti-fibrotic activity of 21 CMM-derived compounds, 11 methanolic extracts of single CMMs and 27 formulae that contained two or more CMMs as mixtures, and found that five compounds, three single CMM extracts and 16 formulae had in vitro anti-fibrotic activities (Hu et al, 2009). Among the five CMM-derived compounds, three flavonoids (quercetin, baicalin and baicalein) showed similar dose-dependent in vitro antifibrotic activities while two non-flavonoids (salvianolic acid B and emodin) showed varied in vitro anti-fibrotic activities with poor dose dependency.…”
Section: Introductionmentioning
confidence: 99%